2017
DOI: 10.1002/app.45982
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of dielectric constant by nanovoids formed through chemical treatment on silica crosslinked polyimide and its effect on properties

Abstract: In this study, 2,7‐diamino‐9‐fluorenol (DAF) has been introduced to bond silica to the main chain of the polyimide (PI) copolymer. DAF contains a hydroxyl group that could covalently bond with silica particles. 4,4′‐(Hexafluoroisopropylidene)diphthalic anhydride (6FDA) and 4,4′‐oxydianiline (4,4′‐ODA) have been used as monomers to form a copolymer with DAF. The variation of silica content was controlled as 5%, 7.5, 10, 12.5 wt %. Variation in silica content contributes to the formation of various size (100–410… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…It is the reason that as the radius of the embedded nanoparticle in the nanocomposites increases, the number of atoms in the surrounding PI consequently increases and, thus, a larger nanoparticle in the nanocomposites can have a greater number of nonbonding pairs . High interaction energy means the particles possess perfect dispersity and satisfactory adhesive in PI matrix, and it can improve the compatibility between PI and SiO 2 . Apparently, surface modification of SiO2 by ICTOS is an effective way to improve the interaction energy between PI matrix and SiO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the reason that as the radius of the embedded nanoparticle in the nanocomposites increases, the number of atoms in the surrounding PI consequently increases and, thus, a larger nanoparticle in the nanocomposites can have a greater number of nonbonding pairs . High interaction energy means the particles possess perfect dispersity and satisfactory adhesive in PI matrix, and it can improve the compatibility between PI and SiO 2 . Apparently, surface modification of SiO2 by ICTOS is an effective way to improve the interaction energy between PI matrix and SiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…It can be explored, the real interaction and performance of two phases after modification, better by defining the characteristics of each component structure inside the materials. PI/SiO 2 nanocomposites have been extensively studied by specific experiments and relevant molecular dynamics (MD) simulation in recent years . Sushmit Goyal et al .…”
Section: Introductionmentioning
confidence: 99%
“…The thermal stability of the samples was tested by TGA, which was shown in Figure . With the thermal analyzer monitoring the weight of samples, the change curve was measured with the heating of the furnace . The analysis results showed that the weight of modified PU can retain more than 95% when the temperature increased at 200 °C, while can be maintained at 100% basically below 100 °C.…”
Section: Resultsmentioning
confidence: 99%